2020
DOI: 10.1111/dth.14391
|View full text |Cite
|
Sign up to set email alerts
|

The influence of topical5%tranexamic acid at pH2.38with and without corundum microdermabrasion on pigmentation and skin surface lipids

Abstract: Tranexamic acid (TA) has anti-hemorrhagic effects; however, oral administration has been found to decrease hyperpigmentation. The aim of the work was to compare the effects of treatment with 5% tranexamic acid in combination with corundum microdermabrasion on skin pigmentation, redness, pH, transepidermal water loss (TEWL), sebum level and hydration of back surface and dorsal surface of the hand skin. Six treatments were performed every week on the back surface and both dorsal surfaces of the hands of 12 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Therefore, we could not compare our results with previous studies. However, both treatment modalities were used previously and their clinical efficacy was found to be superior compared to topical agents (29)(30) This study confirmed the efficacy and safety of laser with or without microdermabrasion, but we could not find any difference between two study groups in terms of clinical response or safety profile. In fact, none of our patients experienced post inflammatory hyperpigmentation which could be due to use of lightening agents before initiation of and during the study as well as using conservative setting for laser treatment.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, we could not compare our results with previous studies. However, both treatment modalities were used previously and their clinical efficacy was found to be superior compared to topical agents (29)(30) This study confirmed the efficacy and safety of laser with or without microdermabrasion, but we could not find any difference between two study groups in terms of clinical response or safety profile. In fact, none of our patients experienced post inflammatory hyperpigmentation which could be due to use of lightening agents before initiation of and during the study as well as using conservative setting for laser treatment.…”
Section: Discussionsupporting
confidence: 67%
“…In a 2020 study by Batory et al on the effect of topical TA 5% with and without microderm abrasion on skin pigmentation and lipids showed significant reduction of melanogenesis and increase hydration of the epidermis 30 …”
Section: Discussionmentioning
confidence: 98%
“…with and without microderm abrasion on skin pigmentation and lipids showed significant reduction of melanogenesis and increase hydration of the epidermis. 30 A 2021 study by Behrangi et al, on patients with melasma identified the benefits of this substance. In this study, patients with melasma were studied by two methods, Nd-Yag Fraction 1064 + microinjection of TA and Nd-Yag Fraction 1064+ oral TA.…”
Section: Discussionmentioning
confidence: 99%